Adubação borácica na cultura do brócolos - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
The Broccoli cultivation is gaining importance in the Brazilian horticulture in recent years, grown mainly by small and medium farmers. The factors that led to this are related to the short cycle of culture, low need for labor and the low seasonality of sales prices on the market. However, for the successful cultivation should be handled culture view agronomic requirements particularly adequate nutritional management. Like other vegetables, broccoli is a very demanding plant macronutrients and micronutrients, especially boron as an essential micronutrient and limiting productivity and quality of inflorescences. The fertilization with boron should be recommended with caution because the boundary between its deficiency and toxicity in plants is narrow and several information published are contradictory as its fertilization. Its deficiency can cause low compression, poor training and dark spots in the inflorescence and the occurrence of physiological abnormality of the hollow stem. The toxicity because burning of edges of the leaves, plant stunting and Death. Therefore, there is a need to reduce or eliminate these problems by using a foliar application of boron supplementing the soil and organic fertilizers as boron source for the culture of broccoli. Thus, the aim of this study was to evaluate the agronomic characteristics of broccoli culture, by applying boron foliar and soil and the influence of organic fertilization with poultry litter in the supply of boron. The work was carried out from two experiments conducted at the experimental farm of the Universidade Estadual de Goiás, Campus Ipameri, Brazil. In experiment 1, the experimental design was a randomized block design (RBD) in factorial 2 x 5, the first factor characterized as without or with application via soil boron (0 and 4 kg ha1 ) and the second factor foliar application of boron in five doses (0, 0.25, 0.5, 0.75, 1 kg ha-1 ). Experiment 2 was conducted in RBD factorial 2 x 5, the first factor characterized as without or with application via poultry litter soil (0 to 10 t ha-1 ) and the second factor foliar application of boron five doses (0, 2, 4, 6 and 8 kg ha-1 ). Therefore, evaluating the boron content of the leaves, stem and inflorescence, fresh pasta, dry and diameter of inflorescence, incidence of hollow stem and the total and commercial productivity. In experiment 1, the largest estimated profitability index was calculated using the estimated dose of 0,68 kg ha-1 B foliar. In experimente 2, the dose up to 8 kg ha-1 to B without application of poultry litter had the highest content of B in the stem between treatments. The use of doses of 6 and 8 kg ha-1 B applied to the soil promoted B content higher than the other treatments. The application of poultry litter promoted the highest values of fresh leaves, inflorescence, leaf B concentration, productivity and gross revenue. The dose of better economic efficiency was gained with the use of 8 kg ha-1 B with the application of 10 t ha-1 of manure.
Keywords: Brassica. oleracea var. italica; micronutriente; ácido bórico; Brassica. oleracea var. italica; micronutrients; boric acid; CIENCIAS AGRARIAS